PUBLIC-PRIVATE AGREEMENT AS A MANAGEMENT PROCESS: A STEP-BY-STEP MODEL OF EFFICIENCY IMPROVEMENT - Kurochka, Pavel; Mazharova, Lina; Polovinkina, Alla (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The aim of the study: to develop recommendations for the comprehensive improvement of the practice of concluding and implementing a PPP agreement. Research methods: analysis, synthesis, logical modeling.In the article the authors substantiate the analysis of the characteristic features of PPP agreements and identified four stages of this process: The first step. The process of initiation (start) of the project; Second step. The processes of execution (implementation) of the project; Third step. Monitoring processes (monitoring) of the project; Fourth step. The process of closing (completion) of the project. There are at least two participants in this process: a "public" partner (state) and a "private partner " - a business with different legal status and resources, as well as having different goals. Each of the four selected stages presents "inputs" (initial action) and "outputs" (final action) separately for each of the participants. In the paper the authors reveal the content of each stage of the process and give step-by-step recommendations to improve efficiency. From the point of view of the authors, consistent implementation of the recommendations presented in the practice of PPP will allow you to get away from the formalism and, in general, to increase the percentage of effective PPP projects.